2021
DOI: 10.15586/aei.v49i2.52
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous intradermal low-dose house dust mite immunotherapy in tropical settings: a valid cost-effective approach for developing nations?

Abstract: Introduction: Aqueous allergen injections, an effective and century-old technique, is considered a second-line approach in daily clinical practice. Inconveniences still surround conventional subcutaneous immunotherapy (SCIT) administration, such as a need for frequent injections, prolonged up-dosing schedules, elevated costs, and the unlikely possibility of a systemic reaction. The intradermal immunotherapy route (IDR) might favorably impact many of the aforementioned issues (Table 1). House dust mite (HDM) al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…However, among the studies, some conflicting evidence has been reported. Three observational studies, two of which were published by Phillips in the early 20th century [ 30 , 31 ], and a recent study by Rondon et al [ 34 ], suggested the benefit of IDIT relative to symptom improvement. However, those three studies did not include control subjects, which makes it impossible to exclude the possibilities of a placebo effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among the studies, some conflicting evidence has been reported. Three observational studies, two of which were published by Phillips in the early 20th century [ 30 , 31 ], and a recent study by Rondon et al [ 34 ], suggested the benefit of IDIT relative to symptom improvement. However, those three studies did not include control subjects, which makes it impossible to exclude the possibilities of a placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…Following the publishing of a pilot study by Hernández et al [ 33 ] that reported a reduction in the total nasal symptom score (TNSS) and the face visual analog scale (fVAS) in eight children with allergic rhinitis treated with IDIT, Rondon et al [ 34 ] recently published a study on IDIT in children diagnosed with perennial allergic rhinitis and a house dust mite (HDM) allergy. Interestingly, instead of using the usual allergen extracts, the authors prepared a flask containing a mixture of Dermatophagoides pteronyssinus / Dermatophagoides farinae and Blomia tropicalis and injected 0.05 mL of the mixture intradermally (approximately 8 AU of Dermatophagoides pteronyssinus / Dermatophagoides farinae and 0.12 mcg of Blomia tropicalis ).…”
Section: Clinical Studies Of Intradermal Immunotherapymentioning
confidence: 99%
“…This is a pivotal issue that will help to overcome the limited technology available for the development of vaccines required for treating patients afflicted with allergies. 42,43) Moreover, continuous efforts are required to approach newer concepts, in particular, the discovery of a novel tool based on severity of the allergy and personal therapy. Exosomes are small vesicles (10-150 nm) secreted from several types of cells to extracellular environment, and include mRNA, lipids and proteins activating target cell function.…”
Section: Novel Approachesmentioning
confidence: 99%
“…Intradermal immunotherapy (IDIT) and epicutaneous immunotherapy (EPIT) are different routes for administering the allergen through the skin. Compared to traditional allergen administration routes, IDIT and EPIT have many benefits, such as shorter treatment duration, lower allergen dose, and no need for adjuvants 113 . Rhinoconjunctivitis patients sensitized to grass pollen and receiving IDIT have been shown to have reduced clinical symptoms, medication consumption, and IgE levels, 114 with the improved clinical effects lasting for up to 2 years 115 .…”
Section: Mechanism‐oriented Treatmentmentioning
confidence: 99%
“…Compared to traditional allergen administration routes, IDIT and EPIT have many benefits, such as shorter treatment duration, lower allergen dose, and no need for adjuvants. 113 Rhinoconjunctivitis patients sensitized to grass pollen and receiving IDIT have been shown to have reduced clinical symptoms, medication consumption, and IgE levels, 114 with the improved clinical effects lasting for up to 2 years. 115 Peanut-allergic children (aged 4-11 years) have also been shown to respond to EPIT with a peanut patch; however, the clinical effect of the patch remains to be fully determined.…”
Section: Intradermal Immunotherapy (Idit) and Epicutaneous Immunother...mentioning
confidence: 99%